Fatal outcome of early postoperative myocardial infarction after implantation of aortic valve bioprosthesis and left internal thoracic artery anastomosis to left anterior descending coronary artery caused by closure of unchanged circumflex coronary artery - Bartczak, Karol; Kula, Piotr; Zwoliński, Radosław; Ammer, Arkadiusz; Kośmider, Anna; Walczak, Andrzej; Banyś, Andrzej; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Acute perioperative myocardial infarction caused by coronary artery embolization after aortic valve implantation is a rare and often fatal postoperative complication. We present a case report of a 67-year-old patient operated on for aortic valve replacement (AVR) and myocardial revascularization (LITA-LAD anastomosis). Myocardial ischemia caused by occlusion of the previously intact circumflex coronary artery occurred in the early postoperative period. Despite a successful balloon angioplasty of the closed artery in the fifth hour after the procedure, the status of the patient did not improve significantly. A decrease in progressive arterial pressure, multiple organ failure, a significant rise of myocardial necrosis markers and the lack of external pacing led to death on the second day after the operation. Acute myocardial infarction after aortic valve replacement caused by occlusion of coronary vessels by calcium debris or thrombosis is a rare postoperative complication, which may be fatal even if the patency of the vessel is promptly restored.